Greece : Update to the Report on the Observance of Standards and Codes, 2002-Fiscal Transparency. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper presents an update to the Report on the Observance of Standards and Codes on Fiscal Transparency for Greece. The government has initiated steps toward improving auditing. The Ministry of Economy and Finance is undertaking a comparative examination of its auditing mechanism against those used by the European Union (EU) and by other advanced economies. It is also making use of the experience gained through the auditing of programs that are financed jointly by national and EU funds. It is intended that all expenditures would be subject to audit prior to expenditure approval.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; EU Legislation; ISCR; Post Program Evaluation; Spending Ministry; Greece